2022
DOI: 10.3390/w14060852
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Heat Exchanger in Solar Desalination: Current Issues and Future Challenges

Abstract: Solar desalination is a process to convert saline water into potable water by the application of solar energy. The enhancement of the distillate output of the solar desalination is low, so it is not considered as a method to produce potable water. A heat exchanger is an important device used for heat transfer applications. The present review article illustrates the application of a heat exchanger with a solar desalination system to enhance the distillate output. In the current review, it is found that the heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Currently, you will find treatments with high efficiencies and affordable costs co-invested as a priority. More studies are needed such as [67,68], which focus on reducing the energy costs of different treatment systems, which would encourage their application. More alternatives are also required for the generation of clean energy that can be input into water treatment [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, you will find treatments with high efficiencies and affordable costs co-invested as a priority. More studies are needed such as [67,68], which focus on reducing the energy costs of different treatment systems, which would encourage their application. More alternatives are also required for the generation of clean energy that can be input into water treatment [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…(5) Te mode of the thermal energy supply was predominantly impulsive than continuous, suggesting insufcient energy to sustain the desalination process characterised by low productivity. (6) At this range of average solar radiation, there was an apparent delay in the vapour delivery to the stages through the vapour make-up tubes from the evaporator. Tis mainly resulted from the cold system's components, which caused the temperature gradient between the vapour and the tube's inner wall to be greater.…”
Section: Low Daily Average Solar Radiationmentioning
confidence: 96%
“…However, the downside of solar stills is their low productivity and efciency. Many methods have been used to improve the solar still's performance, optimise its operation, and enhance the heat transfer processes, such as integrating solar stills with the phase-changing material (PCM), fns, nanoparticle/nanofuids, and solar collectors, incorporating heat exchanger to enhance the distillate yield and productivity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Elsheikh et al, [20] through a literature search examined the importance of the heat exchanger for enhancing the freshwater production in solar desalination. Results indicated that by combining flat plate solar collectors with a heat exchanger the water production rate could be increased.…”
Section: Insert Figure 2 Herementioning
confidence: 99%